Exposure to Dengue Envelope Protein Domain III Induces Nlrp3 Inflammasome-Dependent Endothelial Dysfunction and Hemorrhage in Mice - Lien, Te-Sheng; Sun, Der-Shan; Wu, Cheng-Yeu; Chang, Hsin-Hou (Frontiers in Immunology, 2021)
Typically occurs during secondary infections with dengue viruses (DENVs), dengue hemorrhagic fever (DHF) display vascular damages and abnormal immune responses. The viral factor responsible for the endothelial damages remains elusive. Among the various DENV-related stimuli, during peak viremia, virion-associated envelope protein domain III (EIII) in the plasma of DHF patients reaches a level adequate to induce apoptosis in platelets and megakaryocytes. Thus, EIII may be a virulence factor to cause endothelial damage. In this study, we found that challenges of DENV- and EIII-induced endothelial cell death in vitro. Intriguingly, pyroptosis is the major type of the endothelial cell death, which can be rescued by the inhibitor treatments against Nlrp3 inflammasome. Injections of EIII sufficiently induce endothelial abnormalities; sequential injections of EIII and DENV-NS1 autoantibodies further induce stronger vascular damage, liver dysfunction, thrombocytopenia, and hemorrhage in mice, resembling several typical manifestations in DHF. In the same treatments, Nlrp3 inflammasome deficient mice displayed markedly less pathogenic responses as compared to the wild type animals. These results suggest that Nlrp3 inflammsome is a potential therapeutic target for treating DENV-elicited hemorrhage pathogenesis.